2022
DOI: 10.4149/bll_2023_004
|View full text |Cite
|
Sign up to set email alerts
|

Markers of activation of coagulation in cancer patients

Abstract: BACKGROUND: Prothrombotic tendency is characteristic of tumors. The aim of the study is to investigate the changes in the laboratory parameters for coagulation and fi brinolysis, namely in fi brinogen, thrombinantithrombin complex (ТАТ), tissue factor (ТF), prothrombin fragment (F1+2), antithrombin III (AT III), D-dimer and screening coagulation tests in cancer patients before initiation of chemotherapy. MATERIALS AND METHODS: Levels of F1+2, fi brinogen, ТАТ, AT III, TF, D-dimer, PT, aPTT and TT were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Among them, patients with higher TAT, TM and t-PAIC were more likely to experience thrombotic events, and only TAT was positively correlated with thrombotic events (Spearman r = 0.287, P = 0.019). Our data showed that the activity of ATIII is significantly lower in MPN patients with thrombosis, which can be explained by pathologically increased thrombin formation and increased consumption for the formation of TAT complexes [ 47 ]. In spite of the recognized risk of thrombosis, patients with MPN show little or no abnormalities of traditional coagulation tests such as PT and APTT, perhaps because these are unable to represent the balance between pro- and anti- coagulants nor the effect of platelets and blood cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, patients with higher TAT, TM and t-PAIC were more likely to experience thrombotic events, and only TAT was positively correlated with thrombotic events (Spearman r = 0.287, P = 0.019). Our data showed that the activity of ATIII is significantly lower in MPN patients with thrombosis, which can be explained by pathologically increased thrombin formation and increased consumption for the formation of TAT complexes [ 47 ]. In spite of the recognized risk of thrombosis, patients with MPN show little or no abnormalities of traditional coagulation tests such as PT and APTT, perhaps because these are unable to represent the balance between pro- and anti- coagulants nor the effect of platelets and blood cells [ 32 ].…”
Section: Discussionmentioning
confidence: 99%